Welcoming Guests in Indonesian Traditions: Cultural Studies in Minang, Bugis, Palembang, and Surakarta Dance - Gunawan Wiradharma; Sri Sediyaningsih; Zul Fahmi; Mario Aditya Prasetyo; Cicilia Clara Devi Anggraini (Universitas Medan Area, 2023)
The culture of several regions in Indonesia has a tradition of welcoming guests in the form of traditional dance performances. This study intends to find out the traditions and developments of the welcoming dance at this time. In addition, this study suggests reasons why guests need to be presented with a performance in Minang, Bugis, Palembang and Javanese culture. This research reveals values ​​and meanings so that the characteristics and developments that a culture can carry out in honoring guests can be identified. The method used is qualitative by conducting in-depth interviews with traditional Minang, Bugis, Palembang and Solo artists. The findings in this study indicate that the main motive for guests to be respected and exalted in an area is because guests are considered